Analysis of Students’ Perceived and Actual Weaknesses as Correlates of Performance in Mathematics in Senior Secondary School Certificate Examination in Oyo State Nigeria (2011)
The low levels of mathematical attainment of students at the secondary school level of the educational system in the country have given patriotic Nigerians a worry. This is so because of the universally held assumption of the importance of mathematics to the growth and development of mankind. This study made use of descriptive research design. The studs is restricted to ten local government areas in Ibadan land with one secondary school in each local government. The sample for this study was made up of ten senior secondary schools using simple random sampling procedure to select school in each local government area. Also, simple random sampling was used to pick one arm of Senior Secondary class three in each school, and all the students in the class selected were used for the study. Three research instruments were used with reliability coefficients of0.72, 0.62 and 0.67 respectively. Results from the study indicated that students take mathematics in the senior school certificate examinations without a strong ability to remember, write formulae correctly and to apply the formulae correctly. They also have the wrong notion that mathematics is a difficult subject. To achieve success and enhance performance, the students must as a matter of necessity be able to cultivate mathematical skill so as to be able to better their lot. Students of mathematics who cannot perform basic mathematical operations and their characteristics will surely be unable to answer any question correctly in mathematics. Also thinking that mathematics is a difficult subject, shows how careless and lazy die present day students are. In conclusion, teachers of mathematics are expected to reorganize their teaching methods and personal relationship with their students to stimulate interest and love for mathematics. Better attention should he given to the teaching of English language and mathematics in schools. Teachers should also adopt the pattern of the external examinations, in setting and marking interned examinations. More emphasis on assignments, basic mathematics symbols and basic mathematical operations should be given to the students. Recommendations were made that students should be made to realize and appreciate that no school subject is more difficult or simpler than the others. Professional and highly skilled teachers should be recruited to help improve the status of mathematics in the schools.